The STRATEGI KOMUNIKASI PEMASARAN INDUSTRI KERAJINAN SANGKAR DIAMOND DI MOJOSONGO BOYOLALI - Setiaji, Agus; Hindra Hastuti, Nurnawati; Widiyowati, Estu (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The aim of this research are the author discusses the application of a communication strategy used in industrial marketing for Diamond bird cage crafts in Mojosongo Boyolali. The aim of this research is to find out the communication strategies used by Diamond bird cage craftsmen in marketing their industrial products. The research method used is descriptive qualitative by examining an existing problem and obtaining data directly. In this research, data collection techniques were used through direct observation or on-site observations and interviews with the relevant sources. As well as analyzing the data by examining the problem then based on existing theories. The results of this research are from data obtained by the author from interviews with relevant sources, it can be concluded that diamond cage craftsmen in Mojosongo Boyolali can implement marketing communication strategies in the form of marketing mix strategies in an effort to increase the number of sales after the Covid-19 pandemic. The sales strategy is carried out by holding bird contest events and using the online media Facebook and Instagram. Keyword:Strategy,BirdCage,Marketing